Studying the Stability of One of Non-Linear Autoregressive Relational Models - Abdulghafoor Salim; Hamed Kalaf (Al-Rafidain Journal of Computer Sciences and Mathematics)
Time series are usually built on basic assumptions involving stability, Linearity and normality, these three features are so important in both  estimating and building the time series models. The study of time series involves these assumption and how to manipulate the unstable time series on the basis of which the suitable mathematical models fit for  these series. In this paper, we suggestion the stationarity of one of the non linear -Autoregressive time series models called rational model has been studied which is a fraction whose numerator is the cosine function and its denominator is an exponential Autoregressive models. The singular point and the limit cycle of the models and its stationarity study have been found by adopting the linear approximation technique.